Boundary element analysis of shear deformable shallow shells under harmonic excitation (2014)
In this work, the harmonic analysis of shallow shells using the Boundary Element Method, is presented. The proposed boundary element formulation is based on a direct time-domain integration using the elastostatic fundamental solutions for both in-plane elasticity and shear deformable plates. Shallow shell was modeled coupling boundary element formulation of shear deformable plate and two-dimensional plane stress elasticity. Effects of shear deformation and rotatory inertia were included in the formulation. Domain integrals related to inertial terms were treated using the Dual Reciprocity Boundary Element Method. Numerical examples are presented to demonstrate the efficiency and accuracy of the proposed formulation. Copyright © 2014 Tech Science Press